2019
DOI: 10.4414/smw.2019.20062
|View full text |Cite
|
Sign up to set email alerts
|

Management of brainstem haemorrhages

Abstract: Among spontaneous intracranial haemorrhages, primary non-traumatic brainstem haemorrhages are associated with the highest mortality rate. Patients classically present with rapid neurological deterioration. Previous studies have found that the severity of initial neurological symptoms and hydrocephalus are predictors of poor outcomes. In addition, radiological parameters aim to classify brainstem haematomas according to volume, extension and impact on prognosis. However, previous studies have failed to agree on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 39 publications
(61 reference statements)
0
29
0
6
Order By: Relevance
“…PBSH is the most fatal subtype of intracerebral hemorrhage (ICH) and invariably has a bleak prognosis (1)(2)(3). It has the clinical characteristics of sudden onset, rapid evolution, and high morbidity and mortality (4,5). Multiple studies have investigated the correlation between the prognosis of PBSH and its clinical features, neuroradiological presentation and neurophysiological properties (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…PBSH is the most fatal subtype of intracerebral hemorrhage (ICH) and invariably has a bleak prognosis (1)(2)(3). It has the clinical characteristics of sudden onset, rapid evolution, and high morbidity and mortality (4,5). Multiple studies have investigated the correlation between the prognosis of PBSH and its clinical features, neuroradiological presentation and neurophysiological properties (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Primary brainstem hemorrhage (PBSH) has the worst outcome among all types of spontaneous intracerebral hemorrhage (SICH) [1][2][3]. There was no standardized criteria to diagnose PBSH.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the diagnosis of PBSH is based on the history of hypertension, the clinical and radiological features after excluding other bleeding etiologies such as aneurysm, arteriovenous malformation (AVM), cavernomas and tumor apoplexy within brainstem [3,4]. The management of PBSH remains controversial [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment strategy for brainstem hemorrhage remains controversial. 10 Current guidelines recommend relatively conservative treatment for brainstem hemorrhage; however, this results in a higher mortality rate and poorer prognosis compared with surgical treatment. Many recent studies have found that some patients with brainstem hemorrhage do benefit from surgical intervention.…”
Section: Introductionmentioning
confidence: 99%